Development of Hygiene and Healthy Living Habits Learning Module for Early Childhood Education Teachers - Suyatmin, Suyatmin; Sukardi, Sukardi (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2018)
Abstract   This study aimed to create learning module for kindergarten teachers, on hygiene and healthy living habits. Module that can be used to study about health and additional references on hygiene and healthy living habits. This research is a research and development in 10 steps, by adapting research and development research according to Gall, & Borg's model. Research and development research was conducted by using the following steps: (1) potentials and problems, (2) data collection, (3) product design, (4) design validation, (5) product revisions, (6) product tests, (7) product revisions, (8) product tests, (9) product revisions, and (10) mass production. This research produced a module product to learn about hygiene and healthy living habits for Early Childhood Education that had been tested in schools and validated by media experts and material experts. Evaluation results showed that the module is in accordance with the curriculum, in accordance with the characteristics of growth and development of students, and is easy, interesting, and fun for students.   Keywords : development, hygiene and healthy living habits, early childhood education     Abstrak   Penelitian ini bertujuan untuk membuat modul pembelajaran bagi guru taman kanak-kanak, mengenai kebersihan dan kebiasaan hidup sehat. Modul yang dapat dipakai untuk mempelajari kesehatan dan referensi tambahan mengenai kebersihan dan kebiasaan hidup sehat. Penelitian ini merupakan research and development dalam 10 langkah, dengan mengadaptasi penelitian research and development menurut model Gall, Gall, & Borg's. Penelitian research and development dilaksanakan menggunakan langkah-langkah : (1) potensi dan permasalahan, (2) pengumpulan data, (3)desain product, (4) validasi desain, (5) revisi produk, (6) ujicoba produk, (7) revisi produk, (8) ujicoba produk, (9) revisi produk, dan (10) produksi masal. Penelitian ini menghasilkan produk berupa modul untuk belajar mengenai kebersihan dan kebiasaan hidup sehat untuk pendidikan anak usia dini yang telah diujicoba di sekolah dan divalidasi oleh ahli media dan ahli materi. Hasil evaluasi menunjukkan bahwa modul tersebut sesuai dengan kurikulum, sesuai dengan karakteristik pertumbuhan dan perkembangan siswa, serta bersifat mudah, menarik, dan menyenangkan bagi siswa.   Kata kunci : pengembangan, kebersihan dan kebiasaan hidup sehat, pendidikan anak usia dini